“After School Exercise”: A Program to Promote Students’ Physical Activity IV. Physical Education Teachers’ Perceptions of the Program (Short version of a Greek article) - Syrmpas Ιωάννης; Goudas Μάριος (Inquiries in Physical Education and Sport, 2020)
The purpose of this study was to examine physical education (PE) teachers’ perceptions regarding the functionality of the "After School Exercise" program, the students’ responses to the program, and the program’s effect on students’ afterschool physical activity (PA). Eight PE teachers (N = 4 men, N = 4 women) who implemented the program answered open-ended questions. The content analysis showed that the program, in most cases, was implemented smoothly while where difficulties and problems arose, they were successfully addressed by the PE teachers. PE teachers stated that they were satisfied with the quality of the educational material. They also reported that their students endorsed the program. Interestingly, they reported that many students who had not been actively involved in PE previously participated due to the implementation of the program. Additionally, they stated that the program urged students to learn useful information such as health benefits of exercise, principles of exercise, and the estimation of the intensity of exercise based on heart rate. Finally, the PE teachers reported that due to the implementation of the program their students decided to participate in PA either with their parents, or with their friends in the neighbourhood, or alone at home, or in sports clubs.